2022
DOI: 10.1111/gcb.16084
|View full text |Cite
|
Sign up to set email alerts
|

Climate legacies determine grassland responses to future rainfall regimes

Abstract: Climate variability and periodic droughts have complex effects on carbon (C) fluxes, with uncertain implications for ecosystem C balance under a changing climate. Responses to climate change can be modulated by persistent effects of climate history on plant communities, soil microbial activity, and nutrient cycling (i.e., legacies). To assess how legacies of past precipitation regimes influence tallgrass prairie C cycling under new precipitation regimes, we modified a long‐term irrigation experiment that simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 136 publications
4
30
1
Order By: Relevance
“…e ., centuries‐millennia of differences in water availability) do not find changes in N mineralization with mean AP, which has been attributed to concurrent increases in soil organic C that increase potential N immobilization (Barrett et al., 2002; Feyissa et al., 2021; McCulley et al., 2009). We did not find changes in soil C during the duration of our study (Broderick et al., 2022; Wilcox et al., 2016) or legacies of previous irrigation on soil moisture. Moreover, while historic rainfall patterns may have altered N mineralization via effects on litter chemistry (i.e., belowground plant inputs in this annually burned system), the lack of response of root biomass and chemistry to rainfall treatments (Broderick et al., 2022) suggests that changes in plant C inputs were not the driver of N cycling legacies.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…e ., centuries‐millennia of differences in water availability) do not find changes in N mineralization with mean AP, which has been attributed to concurrent increases in soil organic C that increase potential N immobilization (Barrett et al., 2002; Feyissa et al., 2021; McCulley et al., 2009). We did not find changes in soil C during the duration of our study (Broderick et al., 2022; Wilcox et al., 2016) or legacies of previous irrigation on soil moisture. Moreover, while historic rainfall patterns may have altered N mineralization via effects on litter chemistry (i.e., belowground plant inputs in this annually burned system), the lack of response of root biomass and chemistry to rainfall treatments (Broderick et al., 2022) suggests that changes in plant C inputs were not the driver of N cycling legacies.…”
Section: Discussionmentioning
confidence: 52%
“…Conversely, in previously irrigated prairie now subject to natural water deficits, drought-induced mortality in the microbial community when soils experienced extended dry periods may result in a flush of labile organic N resources (Xiang et al, 2008). Previous results from this experiment revealed that long-term release from water stress resulted in greater MBC, but upon reversal to ambient conditions there was a sharp drop to biomass levels comparable to non-irrigated controls (Broderick et al, 2022). Therefore, in the I→A reversal treatment, release of nutrients from the death of drought sensitive microbes after repeated dry/wet cycles may have contributed to the increased rates of N mineralization in this treatment (Franzluebbers, 1999;Xiang et al, 2008).…”
Section: N Flux Ratesmentioning
confidence: 70%
See 3 more Smart Citations